2018
DOI: 10.1136/bjophthalmol-2018-312025
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of preoperative and postoperative astigmatism in a large population of patients undergoing cataract surgery in the UK

Abstract: There is a significant burden of preoperative astigmatism in the UK cataract population. The available refraction data indicate that this burden is not reduced after surgery with implantation of standard monofocal IOLs. Measures should be taken to improve visual outcomes of patients with astigmatic cataract by simultaneously correcting astigmatism during cataract surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 23 publications
3
36
1
Order By: Relevance
“…The distribution of astigmatism in the large population reported in this study supports evidence from previous smaller studies, both in the UK and worldwide, in pre-operative patients [11,12,2225] and from large consortiums such as CREAM (n = 55,177) [13]. We found that 69%, 29%, 11% and 5% had corneal astigmatism ≥0.5, 1.0, 1.5 and 2.0 dioptres respectively.…”
Section: Discussionsupporting
confidence: 89%
“…The distribution of astigmatism in the large population reported in this study supports evidence from previous smaller studies, both in the UK and worldwide, in pre-operative patients [11,12,2225] and from large consortiums such as CREAM (n = 55,177) [13]. We found that 69%, 29%, 11% and 5% had corneal astigmatism ≥0.5, 1.0, 1.5 and 2.0 dioptres respectively.…”
Section: Discussionsupporting
confidence: 89%
“…An estimated three-quarters of eyes undergoing cataract surgery have astigmatism >0.5 D 1 3 and one-third have >1.0 D. 1 , 2 , 4 The correction of pre-existing astigmatism is fundamental to the goal of achieving emmetropia and increased spectacle independence after cataract surgery. 5 Partial-thickness arcuate incisions, corneal limbal relaxing incisions, and toric IOLs are the most commonly performed procedures to address pre-existing astigmatism at the time of cataract surgery; however, astigmatic outcomes are often suboptimal, particularly in patients with pre-existing dry eye.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, preoperative corneal astigmatism in patients has attracted extensive attention [ 1 , 2 ]. Some studies have observed the distribution of astigmatism in regions such as Brazil [ 3 ], northeastern India [ 4 , 5 ], southern Europe [ 6 ], and the United Kingdom [ 1 , 7 ]. In China, there are only studies reported in the southern, northern, and central [ 8 10 ] regions.…”
Section: Introductionmentioning
confidence: 99%